Waiting for and in gender-confirming healthcare in Sweden: An analysis of young trans people's experiences. Issue 6 (2nd November 2022) - Linander, Ida; Alm, Erika
ABSTRACT: The role of waiting and temporality has been explored in relation to gender-confirming healthcare for adults. However, young people's experiences have been lacking, both in previous research and in the public debates on young trans people's access to gender-confirming medical procedures. This paper explores young trans people's experiences of waiting for and in gender-confirming healthcare in the Swedish context. The analysis draws on 16 semi-structured interviews with young trans people (16-25 years old). The analysis was done using thematic analysis and conceptual work on 'waiting' and 'youth'. The participants described waiting as one of the most challenging aspects of their encounters with the gender-confirming healthcare, and the findings also show that this waiting has consequences for youth's mental health and social life. Social workers can have an important role in providing psychosocial support in times of waiting.